A view from below: what Shack Dwellers International (SDI) has learnt from its Urban Poor Fund International (UPFI). Issue 1 (2nd January 2016) - Schermbrucker, Noah; Patel, Sheela; Keijzer, Nico
Abstract : Cities remain hostile environments for the urban poor. The poor are seen as second-tier citizens blocked by a 'ceiling' of what they can access educationally, financially and in terms of home improvements. This 'ceiling' is created by the institutional structure of cities that include planning regulations, resource flows, financial lending restrictions and political decision-making mechanisms. Based on the experiences of the Urban Poor Fund International (UPFI), this article will explore the range of slum upgrading possibilities that Shack Dwellers International (SDI) affiliates in different countries have undertaken. The Indian and South African cases discussed highlight housing and infrastructure-financing models that are sustainable, pro-poor and not completely dependent on donor grant capital. The examples analysed are drawn from SDI's internal documentation, reporting and materials. The article begins with a brief introduction to SDI and its work around incremental housing improvement; followed by an oversight of the UPFI, stressing key conceptual points before exploring practical examples.